Advances in electric vehicles for a self-reliant energy ecosystem and powering a sustainable future in India - M.A. Majid; Charles Rajesh Kumar J; Arbaz Ahmed (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Electric vehicles (EVs) are essential for solving various mobility, environmental sustainability, and energy security issues. They help reduce greenhouse gas emissions, improve air quality, and promote economic development by creating jobs and developing novel innovations. Despite the numerous benefits of EVs, several difficulties persist, including range anxiety, limited infrastructure for charging, and high starting prices. However, continued breakthroughs in battery innovation, charging infrastructure development, and supporting government regulations steadily reduce these obstacles and increase global EV adoption. Significant EV adoption will necessitate ongoing coordination among governments, stakeholders in the industry, and communities to meet infrastructure requirements, incentivize consumers, and encourage sustainable mobility behaviors. The full potential of EVs can be realized to build a more environmentally friendly, healthier, and more sustainable future for future generations by encouraging innovation, investing in facilities, and raising the public's consciousness. This research aims to analyze current technological advancements in EVs, problems, opportunities, and potential solutions that can serve as the foundation for effective strategies and assist policymakers in formulating plans for target adaptation and achievement in India.